PENINGKATAN KETERAMPILAN PROSES SAINS SISWA PADA MATA PELAJARAN IPA KONSEP TEKANAN ZAT CAIR MELALUI PENDEKATAN STEM (SCIENCE TECHNOLOGY ENGINEERING MATHEMATIC) DI KELAS VIII SMPN 4 KOTA BOGOR - Anis Afifah (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
IMPROVING STUDENTS' SCIENCE PROCESS SKILLS IN IPA SUBJECTS, THE CONCEPT OF LIQUID PRESSURE THROUGH THE STEM (SCIENCE TECHNOLOGY ENGINEERING MATHEMATIC) APPROACH IN CLASS VIII JUNIOR HIGH SCHOOL (SMPN 4 KOTA BOGOR)This research is a Classroom Action Research by providing action on research subjects in two learning cycles. The low science learning outcomes are due to the lack of variation in teachers using the learning model so that students find it difficult to understand the learning material. This study aims to analyze the application of STEM-based learning in improving science learning outcomes of students at SMPN 4 Bogor. This research is a Classroom Action Research which is carried out in 2 cycles, each cycle is implemented with STEM-based learning. The subjects of this study were 35 students. Data collection techniques through tests and interviews. The data analysis technique used is descriptive analysis. The results of this study show that at the beginning of the observation the average value was only 44.26, in cycle I became 64.40 and cycle II increased significantly to 83.90 . Absorption and Completeness Learning outcomes in the initial observation (observation) before the action were 40.22% and 24.78%, the first cycle showed that the absorption and completeness of the class became 72.45% and 74.89% which were in the very category. medium high in the second cycle the absorption and completeness of the class increased rapidly to 94.76% and 98.32%. It can be concluded that STEM-based learning can improve science learning outcomes. The implication of this research has the impact of creating a learning atmosphere to be more active so that it can improve student learning outcomes.